(untitled) (Rome, 2001)
This multivolume field guide covers the species of interest to fisheries of the major marine resource groups exploited in the Western Central Pacific. The area of coverage includes FAO Fishing Area 71 and the southwestern portion of Fishing Area 77 corresponding to the South Pacific Commission mandate area. The marine resource groups included are seaweeds, corals, bivalves, gastropods, cephalopods, stomatopods, shrimps, lobsters, crabs, holothurians, sharks, batoid fishes, chimaeras, bony fishes, estuarine crocodiles, sea turtles, sea snakes and marine mammals. The introductory chapter outlines the environmental, ecological and biogeographical factors influencing the marine biota as well as the basic components of the fisheries in the Western Central Pacific. Within the field guide, the sections on the resource groups are arranged phylogenetically according to higher taxonomic levels such as class, order and family.
Keywords: Sinh vật biển,Marine organisms; Nhận dạng,Identification; Khu vực Thái Bình Dương,Pacific Area